Genomic mapping identifies two genetic variants in the MC1R gene for coat colour variation in Chinese Tan sheep - Gebreselassie, Gebremedhin (PLoS One, 2020)
Coat colour is one of the most important economic traits of sheep and is mainly used for breed identification and characterization. This trait is determined by the biochemical function, availability and distribution of phaeomelanin and eumelanin pigments. In our study, we conducted a genome-wide association study to identify candidate genes and genetic variants associated with coat colour in 75 Chinese Tan sheep using the ovine 600K SNP BeadChip. Accordingly, we identified two significant SNPs (rs409651063 at 14.232 Mb and rs408511664 at 14.228 Mb) associated with coat colour in the MC1R gene on chromosome 14 with −log10(P) = 2.47E-14 and 1.00E-13, respectively. The consequence of rs409651063 was a missense variant (g.14231948 G>A) that caused an amino acid change (Asp105Asn); however, the second SNP (rs408511664) was a synonymous substitution and is an upstream variant (g.14228343G>A). Moreover, our PCR analysis revealed that the genotype of white sheep was exclusively homozygous (GG), whereas the genotypes of black-head sheep were mainly heterozygous (GA). Interestingly, allele-specific expression analysis (using the missense variant for the skin cDNA samples from black-head sheep) revealed that only the G allele was expressed in the skin covered with white hair, while both the G and A alleles were expressed in the skin covered with black hair. This finding indicated that the missense mutation that we identified is probably responsible for white coat colour in Tan sheep. Furthermore, qPCR analysis of MC1R mRNA level in the skin samples was significantly higher in black-head than white sheep and very significantly higher in GA than GG individuals. Taken together, these results help to elucidate the genetic mechanism underlying coat colour variation in Chinese indigenous sheep.